Kasus im Korpus Zu Struktur und Geographie oberdeutscher Kasusmorphologie - Ellsäßer, Sophie (Empirische Linguistik / Empirical Linguistics, 2020)
This study provides a new methodological approach to the corpus-based analysis of case marking in spoken language and provides the first quantitatively based insights into the construction of a dialectal case system and its interaction with morphosyntactical and semantic categories as well as the morphological organisation of space by linking morphological-theoretical questions with typological and dialect-geographical questions.